Computational proteomics analysis of Taphrina deformans for the identification of antifungal drug targets and validation with commercial fungicides - Ahmad, Waqar; Rahman, Ziaur; Khan, Haji; Nawab, Javed; Rahman, Hazir; Siddiqui, Muhammad Faisal; Saeed, Wajeeha (Frontiers in Plant Science, 2024)
Taphrina deformans is a plant pathogenic fungus and a responsible agent for causing peach leaf curl disease. The Taphrina deformans affect Peach fruit production and contribute to global economic losses. Commercial fungicides may provide temporary relief, however their overuse resulted in adverse environmental consequences as well as leading to drug resistant strains of T. deformans. Therefore, the discovery of novel drug targets for future synthesis of antifungal drugs against Taphrina deformans is needed. Here, we studied the Taphrina deformans by computation proteomic approaches. The whole genome and proteome of T. deformans was subjected to subtractive proteomics, high throughput virtual screening and molecular dynamic simulations.We employed subtractive proteomics analysis of 4,659 proteins extracted from UniProtKB database using subtractive proteomics; after filtering out homologous and non-essential proteins we identified 189 essential ones including 9 that participated in crucial metabolic pathways of pathogen. These proteins were categorized as nuclear (n=116), cytoplasmic (n=37) and membrane (n=36). Of those essential proteins Glutamate Cysteine Ligase (GCL) emerged as one promising target due to its essential function for glutathione biosynthesis process which in facilitating T. deformans survival and pathogenicity. To validate GCL as an antifungal target, virtual screening and molecular docking studies with various commercial fungicides were carried out to better characterize GCL as a drug target. The data showed that strong binding affinities for Polyoxin D, Fluoxastrobin, Trifloxystrobin, and Azoxystrobin within active site of GCL. Polyoxin D showed strong affinity when measuring docking score at -7.34kcal/mol while molecular dynamics simulations confirmed stable interactions (3 hydrogen bonds, 2 hydrophobic, and 1 salt-bridge interaction) supporting our findings that GCL represents an excellent target for antifungal drug development efforts. The results showed that GCL as an innovative target for future fungicide designs to combat T. deformans infections, providing an avenue towards creating more effective peach leaf curl disease treatments while mitigating environmental harm caused by current use.